Case Report: Next-Generation Sequencing in Diagnosis of Atypical Aspiration Pneumonia - Quan Zhang; Wei Xu; Fei Peng; Si Lei; Yanjun Zhong; Jun Yi; Shangjie Wu (Frontiers Media S.A., 2022)
Since the pandemic of Corona Virus Disease 2019 (COVID-19), especially in the centers most affected, the symptoms such as fever, cough, myalgia or fatigue, and radioactive signs typically related to COVID-19 like ground-glass opacity (GGO) often distract the attention of physicians from other diseases. Aspiration pneumonia and COVID-19 share similarities in some aspects. There may be risk of misdiagnosis in the case of considering radiological patterns of pneumonia. Early diagnosis and treatment often greatly improve prognosis. We herein reported a case of 40-year-old patient who underwent chest CT scan with the discovery of ground-glass opacity, intralobular reticular opacity and interlobular septal thickening, consolidation, and air bronchogram sign, which were mainly located in the middle and upper lobes of the right lung. It was considered to be infection related pneumonia based on the negative reverse transcription-PCR (RT-PCR) result of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The next-generation sequencing (NGS) of bronchoalveolar lavage fluid (BALF) was performed and detected nucleic acid sequences of Klebsiella sp. Consequently, the patient accepted sensitive intravenous antibiotics therapy for 13 days and had a remarkable clinical and radiological improvement. His case was followed up through imaging procedures. Because of possible radiologic and clinical similarities between aspiration and COVID-19 pneumonia, COVID-19 can be of some value in proposing a differential diagnosis of aspiration pneumonia. Clinicians could suggest a correct diagnosis by careful examination of the CT images together with attention to the clinical history and judicious utilization of NGS, especially.